Concealed Enterovesical Fistula Associated with Forgotten Intra-Abdominal Haemostat and Intravesical Towel - Ademola Alabi Popoola; J. O. Bello; G. G. Ezeoke; K. T. Adeshina; A. Fadimu (Case Reports in Urology)
Introduction. Enterovesical fistula is rare and is often caused by bowel inflammatory diseases and tumours in the urinary bladder or the intestine with local infiltration of bowel or bladder, respectively. The fistula usually presents with lower urinary tract symptoms, pneumaturia, and faecaluria or with food particles in the urine. Intra-abdominal retained surgical foreign bodies have also been reported as causes. Case Presentation. A case of atypical presentation in a woman with enterovesical fistula following abdominal hysterectomy. Investigations confirmed the presence of surgical towel in the urinary bladder and a pair of artery forceps in the abdomen. The towel was removed at cystoscopy after which she presented with food particles in the urine. She later had laparatomy to remove the haemostat and to repair the fistula. Discussion. A typical presentation of enterovesical fistula delayed the diagnosis and treatment in this patient. Conclusion. Managing patients with recurrent urinary tract infection after abdominal operation should include appropriate imaging of the abdomen with emphasis on pelvic organs. Also, surgical operation should always be given the best shot the first time and strict operation room standards and guidelines should always be followed.